PELATIHAN PENGOLAHAN DATA PENELITIAN MENGGUNAKAN APLIKASI SPSS - Sudarso, Hendra; Fahrudin, Ahmad; Suryati, Suryati; Fajriana, Fajriana; Sappaile, Baso Intang (Universitas Pahlawan Tuanku Tambusai, 2024)
Pelatihan